2013
DOI: 10.5455/musbed.20130118092619
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Dietary Phenolics and Antioxidant Properties of Vegetables Depends on Cooking Methodology

Abstract: Ya zış ma Ad re si / Add ress rep rint re qu ests to: Indrani Kalkan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, not all cooking methods increase the antioxidant capacity of the eggplant. Frying caused 50% losses in antioxidant activity (Kalkan & Yücecan, 2013).…”
Section: Antioxidant Capacity Of Eggplantmentioning
confidence: 99%
“…However, not all cooking methods increase the antioxidant capacity of the eggplant. Frying caused 50% losses in antioxidant activity (Kalkan & Yücecan, 2013).…”
Section: Antioxidant Capacity Of Eggplantmentioning
confidence: 99%
“…Meanwhile, high heat applied during frying would lose most phenolic content compared to other cooking methods, i.e. which caused thermal decomposition of the phenolic compound during frying (Turkmen et al, 2005;Kalkan and Yucecan, 2013).…”
Section: Antioxidant Contentmentioning
confidence: 99%
“…This is due to polyphenols compound could dissolve in boiled water, thus boiling caused a higher reduction in antioxidant activity in vegetables compared to steaming (Hwang et al, 2012;Sengul et al, 2014). Meanwhile, Kalkan and Yucecan (2013) reported that frying caused the highest loss of antioxidant activity in vegetables. Zhang et al (2011) suggested that long term exposure to the high temperature degraded the antioxidant compound in bamboo shoot.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The presence of phenolic and flavonoids compounds in Napier grass has shown its nutritional value and also its antioxidant role in protecting organism from free radicals that cause ageing and chronic diseases such as cancers, diabetes and cardiovascular diseases (Gramza et al, 2005;Irina and Mohamed, 2012;Kalkan and Yücecan, 2013;Gunathilake and Ranaweera, 2016;Nobosse et al, 2017). Therefore, based on the result of TPC and TFC of this study, consumption of Napier grass tea could be beneficial to body health.…”
Section: Determination Of Total Flavonoid Content (Tfc)mentioning
confidence: 99%